RESPONS MUZAKKI PEGAWAI NEGERI SIPIL KOTA LANGSA TERHADAP KEWAJIBAN ZAKAT MENURUT QANUN ACEH NOMOR 10 TAHUN 2007 TENTANG BAITUL MAL (STUDI TAHUN 2013) - Zainal Muttaqin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
Qanun Aceh Number 10 Year 2007 About Baitul Mal has set up obligations of civil servants. But the response muzakki civil servants Langsa City to zakah obligation is a legal problem is still debating. Based on that problem, this research aims to know the rules of zakah civil servants according to Qanun Aceh and to analyze the response muzakki civil servants Langsa City to zakah obligations of civil servants in Aceh. This Research methods is descriptive empirical legal research approach with qualitative research. Instrument collection of data that is used in this research is an interview and data literature. From interviews with 100 PNS Langsa City, researchers found some field findings among others are; assumption that the civil servants profession zakah is not obligatory, assuming that there is no right mustahiq of the money profession civil servants, assumption that the civil servants earning must be paid is only basic salary, not allowances salary or other acceptance, assumtion that civil servants profession zakah which has reached nishab only obliged to be paid after up to one year, assumtion that payment of money 2.5 % from the amount of payment before deduction for basic needs, debt and credit is contrary to some study fiqh.